2018
DOI: 10.1039/c7gc03780e
|View full text |Cite
|
Sign up to set email alerts
|

A palladium-catalyzed dehydrative N-benzylation/C–H benzylation cascade of 2-morpholinoanilines on water

Abstract: A strategy for the palladium-catalyzed dehydrative tandem benzylation of 2-morpholinoanilines with benzyl alcohols has been developed. This cascade reaction is devised as a straightforward and efficient synthetic route for N-(1,2-diphenylethyl)-2-morpholinoanilines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…On the basis of these results and our previous report, [18] we propose a catalytic mechanism for the dehydrative coupling of 1-aminoisoquinoline (1a) with benzyl alcohol (2a) in water as illustrated in Scheme 5. First, oxidative addition of hydrated alcohol 2a to the water-soluble Pd 0 /TPPMS catalyst affords the cationic π-benzylpalladium(II) complex A (step 1).…”
Section: Mechanistic Considerationssupporting
confidence: 62%
See 2 more Smart Citations
“…On the basis of these results and our previous report, [18] we propose a catalytic mechanism for the dehydrative coupling of 1-aminoisoquinoline (1a) with benzyl alcohol (2a) in water as illustrated in Scheme 5. First, oxidative addition of hydrated alcohol 2a to the water-soluble Pd 0 /TPPMS catalyst affords the cationic π-benzylpalladium(II) complex A (step 1).…”
Section: Mechanistic Considerationssupporting
confidence: 62%
“…[17] We recently developed a new environmentally benign borrowing hydrogen methodology for dehydrative coupling of 2-aminopyridines under basefree aqueous conditions. [18] However, we could not provide enough support for the catalytic pathway and the scopes of the pyridine nucleophiles were limited. In this paper, we describe new insights into the chemistry of the palladium-catalyzed N-benzylation pathway via π-benzylpalladium(II) complexes in water and the development of a borrowing hydrogen process as a new synthetic route for series of N-benzylated aminoisoquinolines (Scheme 1B).…”
Section: Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hikawa et al. reported a palladium‐catalyzed dehydrative N‐benzylation with benzyl alcohol in water . They suggested that water activated the sp 3 C−O bond of the alcohol via hydrogen bonding with formation of the π‐benzylpalladium(II) complex.…”
Section: Methodsmentioning
confidence: 99%
“…In the next step, a second amine and methyl propiolate react with the dehydrated compound with benzyl alcohol in water. [19,20] They suggested that water activated the sp 3 CÀ O bond of the alcohol via hydrogen bonding with formation of the π-benzylpalladium(II) complex. A similar type of effect, based on a hydrogen-bonding network of water molecules, could accelerate the hydroxyl group elimination in our 1,4-DHP formation.…”
mentioning
confidence: 99%